Pengaruh Kegiatan Finger Painting Terhadap Motorik Halus Anak Pada Kelompok B di Tk Pembina HKBP Tarutung (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
The aim of this research to determine the effect of finger painting activities on the fine motor skills of group B children at the HKBP Tarutung Pembina Kindergarten. The method used in this research is a quantitative research method with descriptive statistics. The population was all children aged 5-6 years, totaling 93 people an a sample of 17 people was determined. Data was collected using a positive closed questionnaire with 30 items. The results of data analysis show that there is an influence of finger painting activities on the fine motor skills of children in group B at the Tarutung HKBP Pembina Kindergarten: 1) Test analysis requerements: a) positive relationship test obtained by rxy = 0.617 < rtabel (a=0,05,n=17) = 0,482. Thus is known that there is an influence between variable there is an influence between variable thus Ha is accepted and Ho is rejected.